ANALISIS PERBANDINGAN KINERJA KEUANGAN BADAN USAHA MILIK DESA (BUMDES) DI KABUPATEN ROKAN HULU - Afrijal, Ramadhani (Jurnal Ilmiah Cano Ekonomos, 2016)
This study aimed to analyze the financial performance of Badan Usaha MilikDesa (BUMDes) in Rokan Hulu district using financial ratios choice. In analyzing the dataobtained, the method used is descriptive analysis and comparative analysis. Descriptiveanalysis using financial ratio analysis method is selected while a comparative analysis wasused to compare the financial performance BUMDes in Rokan Hulu in 2014 in accordancewith the results of the calculation of financial ratios. Based on the results of the studyshowed that the average current ratio BUMDes in Rokan Hulu by 277% (very good).Average Debt to Asset Ratio (DAR) by 42% (good). The average ratios Return on Assets(ROA) of 8% (good). The average ratio of Total Asset Tun Over (TATO) of 0.23 times (notgood).